MEJA DAN KURSI BELAJAR ERGONOMIS MENGURANGI KELUHAN MUSKULOSKELETAL SISWA SMP TUNAS DAUD DI DENPASAR - Biomi, Agnes Ayu; Dharmayanti, Cokorda Istri (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 7 No 2 (2021): Volume 7 No 2 December 2021DO - 10.24843/JEI.2021.v07.i02.p05, 2021)
From a preliminary study conducted on 10 private junior high school students in Denpasar, data were obtained that 40% of students experienced complaints of dizziness, 50% glare and 10% sore eyes. In addition, students' musculoskeletal complaints were caused by the size of the chairs and study desks not in accordance with the student's anthropometry and as a result of a monotonous environmental condition, causing less stimulus or stimulation to affect student concentration during learning. With the above background, a research was conducted with The same-subject design involved 26 students with an age range of 13-15 years. The study was conducted for 3 days in a row, namely on Monday, Tuesday and Wednesday by measuring the anthropometry of the student's body using a super brand anthropometer 686, musculoskeletal complaints with the Nordic Body Map before and after repairs were made. Data were analyzed using paired t-test at the significance level of p=0.005. The results showed that the mean of musculoskeletal complaints before successive improvement was 27.44 ± 0.27; 26.94 ± 0.61 and 27.00 ± 0.55. An unnatural learning attitude caused by the chair being not high enough, an additional 2 cm of chair was made to compensate for the height of the table which had been adjusted to the popliteal height and elbow height in the sitting position. By making improvements to the chair can reduce musculoskeletal complaints by 42, 14%. From the research, it can be concluded that repairing tables and chairs  can reduce students' musculoskeletal complaints and it is suggested that the layout of these improvements will be used in the future for students with an age range of 13-15 years.